National and provincial burden of lung cancer attributable to fine particulate matter air pollution in China, 1990–2021: a systematic analysis of the Global Burden of Disease Study 2021 - Yixuan Jiang; Peng Yin; Renjie Chen; Haidong Kan; Maigeng Zhou (The Lancet Regional Health. Western Pacific)
Background: Fine particulate matter (PM2.5) air pollution is recognized as the major environmental risk factor contributing to global mortality and disability. It has been linked with lung cancer, which is the leading cause of cancer-related death both worldwide and in China. This study aims to assess the temporal trends and spatial distribution of the lung cancer burden attributable to PM2.5 exposure in China from 1990 to 2021. Methods: Exposure to PM2.5, including both ambient air pollution and household pollution from solid fuels, was estimated across all provincial administrative units in China. Using the methodology framework and analytical strategies of the Global Burden of Disease Study 2021, we calculated the number, age-standardized rate, and percentage of deaths and disability-adjusted life years (DALYs) from lung cancer attributable to PM2.5 from 1990 to 2021 at the national and provincial level. Comparisons were performed by sex, age, and province. Findings: In 2021, PM2.5 pollution resulted in 211.4 thousand deaths and 4894.7 thousand DALYs from lung cancer in China, accounting for 26.0% of total lung cancer deaths and 25.9% of DALYs. Among these, 178.6 thousand deaths and 4125.8 thousand DALYs were attributed to ambient PM2.5 exposure, while 32.6 thousand deaths and 766.7 thousand DALYs resulted from household exposure. The age-standardized lung cancer death rate attributable to PM2.5 pollution in 2021 was 10.1 per 100,000, with the rate in males (14.5) being more than twice that of females (6.4). This sexual difference was more pronounced for ambient exposure compared with household exposure. The lung cancer burden increased with age, with the highest observed among elderly people (80+ years). Geographically, the PM2.5-related lung cancer burden varied across provinces. The burden from ambient PM2.5 was predominantly observed in North and Northeast China (e.g., Tianjin and Liaoning), while that of household PM2.5 was concentrated in Southwest China (e.g., Yunnan and Guizhou). From 1990 to 2021, the age-standardized lung cancer death and DALY rates attributable to PM2.5 decreased by 25.5% and 32.6%, respectively. Similar trends were found across different age groups and sexes. This reduction was mainly driven by decreased burden from household PM2.5, particularly in regions with better economic development (e.g., Beijing, Tianjin, and Shanghai). In contrast, the lung cancer burden due to ambient PM2.5 continued to increase, especially in Central and North China (e.g., Henan and Hebei), and only began to decline after 2015. Interpretation: Despite the decrease in lung cancer burden from total and household PM2.5 in China from 1990 to 2021, ambient PM2.5 remains a critical challenge. Higher burden was observed among males, the elderly, and people from certain provinces. Our findings underscore the need for geographically-tailored and population-specific air pollution control measures, especially for ambient PM2.5, to efficiently reduce lung cancer burden in China. Funding: National Natural Science Foundation of China (82030103), National Key Research and Development Program of China (2022YFC3702701), China Postdoctoral Science Foundation (2023M740649).